Reciprocal translocation between chromosomes 8 and 9 in atypical chronic myeloid leukaemia. - Oscier, D G (1985)
A balanced translocation t(8;9) (p11;q34) was present in the peripheral blood, bone marrow, and spleen cells of a patient with Ph negative chronic myeloid leukaemia. Subsequent transformation into acute leukaemia was associated with the emergence of trisomy 8 and der(8)(8qter----cen----8p11::9q34----9qter). This is the third reported case of t(8;9) (p11;q34) and raises the question of the role of c-abl in the pathogenesis of this myeloproliferative disorder.